2020
DOI: 10.1093/rheumatology/keaa884
|View full text |Cite
|
Sign up to set email alerts
|

Base of thumb osteoarthritis in UK interface services—a cohort and survey-based study to assess current practice

Abstract: Aim Base of thumb osteoarthritis (BTOA) is a common age-related disease which has a significant negative impact upon quality of life, while little is known about structure and pathways of interface services. Our aim was to assess disease burden, referral pathways, service structure and management pathways in UK interface services. Patients & Methods A structured questionnaire was carried out with a participating clinician… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The interview schedule was developed based on a previous work that has described the CMCJ OA care pathways in the UK. 4 It covered five topics of interest relating to general management approach, the role of exercise, surgery and steroid injection, and clinical trial design ( Table III ). All participants provided verbal consent before the start of each interview.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The interview schedule was developed based on a previous work that has described the CMCJ OA care pathways in the UK. 4 It covered five topics of interest relating to general management approach, the role of exercise, surgery and steroid injection, and clinical trial design ( Table III ). All participants provided verbal consent before the start of each interview.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] The majority of thumb CMCJ OA pain is managed in primary care settings or by referral to musculoskeletal services, which are largely run by physiotherapists or occupational therapists. 4 Therapybased interventions vary and often include patient education, analgesia, exercises, joint protection, assistive devices, splints, and steroid injections. 4,5 Our previous work has demonstrated that this treatment appears fairly common across the UK, although there are variations regarding the use of steroid injections.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations